1999
DOI: 10.1016/s0038-1098(99)00277-x
|View full text |Cite
|
Sign up to set email alerts
|

Optical study of the metal–nonmetal transition in NiS

Abstract: Optical reflectivity study has been made on the hexagonal (NiAs-type) Ni 1−δ S in order to probe its electronic properties, in particular those associated with the metal-nonmetal transition in this compound. Samples with δ=0.005 and 0.02 are studied, which have transition temperatures Tt=246 K and 161 K, respectively. A pronounced dip appears in the reflectivity spectra upon the transition, and the optical conductivity spectra show that the electronic structure below Tt is similar to that of a carrier-doped se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
3
21
1
Order By: Relevance
“…It is observed that the plot is linear and the optical band gap respectively, as can be seen from the plots. It was found that the band gap energy of the resultant nanoparticles showed marked increment as compared with that of bulk NiS (0.2 eV) [22]. The decrement of particle size, which increased the optical band gap energy of the nanoparticles, indicates the presence of quantum confinement effect, which is consistent with the previous theoretical arguments by Brus [23].…”
Section: Resultssupporting
confidence: 89%
“…It is observed that the plot is linear and the optical band gap respectively, as can be seen from the plots. It was found that the band gap energy of the resultant nanoparticles showed marked increment as compared with that of bulk NiS (0.2 eV) [22]. The decrement of particle size, which increased the optical band gap energy of the nanoparticles, indicates the presence of quantum confinement effect, which is consistent with the previous theoretical arguments by Brus [23].…”
Section: Resultssupporting
confidence: 89%
“…Besides, the transition temperature is lowered sharply with increasing Ni vacancy concentration and the transformation disappears when the vacancy contents exceed $ 4%. Similar behavior is also observed with applied pressure: the transition doesn't happen at pressure above $2 GPa [9]. Those related experimental results could be found in Refs.…”
Section: Introductionsupporting
confidence: 82%
“…The absorption data have been determined from transmission and reflection spectra (see Figure S2). By extrapolating the linear part of the data in the Tauc plots, optical bandgap values of about 0.7 eV were obtained for both thin films [79].…”
Section: Preparation Of Nickel Sulfide Thin Filmsmentioning
confidence: 99%